Investigasi Kebutuhan Rehabilitasi Konstruksi Bangunan Utama Dan Saluran Primer D.I Nangewer Kabupaten Purwakarta - Ernawan, Deny; Dwipayana Raspati, Adhitya (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Irrigation is one of the best ways to meet farmers' water needs which will have an impact on increasing the productivity of agricultural products, D.I. Nagewer in Purwakarta Regency requires improvements to the construction of irrigation networks, this is indicated by the decline in agricultural product yields in the last five years. The entire irrigation network system of D.I. Nangewer requires an increase to the level of technical irrigation, namely to facilitate the operation of the irrigation network by farmers. The method used is qualitative descriptive analysis with direct observation in the form of topographic surveys, inventory of existing construction as well as hydrological and hydraulic surveys of existing irrigation networks, interviews with farming communities to find out actual data on damage and construction needs for irrigation networks and carrying out special mathematical analysis related to the results of topographic and hydrological surveys. , hydraulics. The results of the research include potential flood discharge for a return period of 2 years to 100 years in rivers used as the main source of irrigation water, information on existing discharge and mainstay discharge, construction dimensions for main buildings and primary channels resulting from evaluation of existing designs and the need for construction rehabilitation work plans.